The relationship between work performance and work design of academic librarians in Malaysia - Mohd Faizal, Hamzah (2019)

(untitled)
Issues related to individual performance, well-being, and competencies (COM) are never-ending. Researchers are still examine and observe the dimension and motivation factors that influence employees’ performance. By looking for a new research setting, work performance (WP) and work design (WD) among academic librarian in Malaysia is the central theme for this study. The discussions related to the theme have been well documented to understand the subject matter. The researcher has also unveiled the connotation of COM into the proposed relationship. The study has identified several research gaps which lead to this study. In the current practice, WP of the academic librarian was measured based on the task fulfillment per se. WD has been completely ignored during the design of the job scope of the academic librarian. The previous study on WP and COM among librarian botched to provide an empirical study on WD. Hence, there is lack of established theories, model and framework can be referred. As the results, academic librarians experience overload role and tend to burnout because of the transformation of the job scope. Besides that, the futility of previous studies in providing the evidence of the relationship between WD and librarian core COM. Moreover, there is no framework consisting of the WD, COM, and WP ever exist in library research. With that, three main objectives derived, namely, to examine the level of WD and WP of Malaysian academic librarians, to examine the effect of librarians’ WD and COM on WP and to examine whether librarians’ COM mediate the relationship between WD and WP. In the context of this study, the proposed dimension to study WP and WD are focusing on task-oriented fulfillment. There are two WP dimensions proposed which are task performance and contextual performance. Similarly, two dimensions of WD have been adopted, namely, task characteristic and knowledge characteristic. To mediate the relationship, seven cores of COM were adapted based on the previous studies. A set of questionnaire was distributed right after the pre-testing and pilot testing of the instrument. The questionnaire was distributed to the entire academic librarians in public universities in Malaysia. SPSS version 22 was used to analyze the first objective. In addition, the researcher used the SmartPLS version three to fulfill the second and third objectives. The initial measurement analysis was conducted to identify the problematic items in the proposed framework. The structural model analysis indicates that the proposed relationship between the dimensions is significantly prediction to WP. With that, this study has offered three contributions in the category of empirical contribution, theoretical contribution and practical contribution. The study provides tested empirical evidence of the relationship towards the academic librarian. The proposed framework may serve as the guidance for future researchers to conduct a further study on WD, COM and WP. Moreover, the instrument developed and the analysis for this study can be reused to measure the level of WP and WD among another category of the librarian.